2008 2nd ICTON Mediterranean Winter 2008
DOI: 10.1109/ictonmw.2008.4773127
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum slicing for low cost wavelength division multiplexing

Abstract: The key features of spectrum slicing are discussed in the context of the provision of low cost customer access as an alternative to laser systems. The history of the method is presented followed by an outline of performance analysis techniques. Following from this, system results are introduced from on-off keying leading to promising outcomes from the use of more sophisticated coding and modulation methods. There is also discussion of the use of shared optical preamplifiers that can deliver increased throughpu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…It is shown that flat-top AWG has narrower spectral filter shape than Gaussian type AWG. Wider filter shape leads to larger slice width, higher resultant slice's power and optical signal dispersion (Leeson and Sun, 2008;Spolitis et al, 2012). In OptSim software we simulated flat-top type AWG filter shape using Raised Cosine optical filter's transfer function but using Super-Gaussian transfer function we approximate Gaussian AWG filter shape .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is shown that flat-top AWG has narrower spectral filter shape than Gaussian type AWG. Wider filter shape leads to larger slice width, higher resultant slice's power and optical signal dispersion (Leeson and Sun, 2008;Spolitis et al, 2012). In OptSim software we simulated flat-top type AWG filter shape using Raised Cosine optical filter's transfer function but using Super-Gaussian transfer function we approximate Gaussian AWG filter shape .…”
Section: Resultsmentioning
confidence: 99%
“…One of basic techniques available in WDM PON systems in order to reduce the cost of components and simplify the passive network architecture is spectrum slicing technique where incoherent broadband light source (BLS) is used. Such a BLS is a good candidate for generating equally spaced multi-wavelength channels (Leeson and Sun, 2008;El-Sahn et al, 2010). The aim of spectrum slicing is to employ a single BLS for transmission on a large number of wavelength channels ( Figure 2).…”
Section: Spectrum-slicing Technique Of Broadband Ase Source Using Arrmentioning
confidence: 99%
See 1 more Smart Citation
“…The bitrate of the investigated data transmission system is chosen to be 1.5 Gbit/s per channel and also 1.25 Gbit/s to test lower transmission speeds. Transmission bitrate in such a type spectrum-sliced optical communication systems is limited by the excess intensity noise (EIN) evaluated in the articles [25,26], where it is discussed that particular noise is created by the spontaneous-spontaneous beating between different wavelength components of the spectrum-sliced light. Moreover, articles [27,28] propose that the intensity noise can be suppressed by gain saturated semiconductor optical amplifier (SOA), which amplifies incoming carrier spectral slice, as well as suppresses EIN, which rises from the spontaneous-spontaneous beating between different wavelength components of the spectrally sliced incoherent broadband ASE light source.…”
Section: Description Of Developed Experimental Combinedmentioning
confidence: 99%